FREKUENSI SOIL TRANSMITTED HELMINTHS PADA SISWA SEKOLAH DASAR NEGERI DESA SENAMAT KECAMATAN PELEPAT KABUPATEN BUNGO JAMBI - Indriati, Gustina (Sainstek : Jurnal Sains dan Teknologi, 2011)
high. Most of health problem caused by infection of intestinum Soil transmitted helminth, frequently infected children. Based on this problem, the study is done to find out the frequensi of STH on the studens of SD Desa Senamat Kecamatan Pelepat Kabupaten Bungo, Jambi Province. The reseacrh is done on August 2010 at SDN 02/II Senamat and SDN 49/II Senamat. The reseacrh used Total sampling Technique. The amount of the sample of this study is 151. The result of this study shows that there are 30,34% infected by STH (Ascaris lumbricoides 22,47% ; Trichuris trichiura 0%, and 11,23% infected by cacing tambang, and infected by Ascaris lumbricoides and cacing tambang 3,37%). While, there are 41,49% infected by STH (Trichuris trichiura 0%, infected cacing tambang 19,35%, and infected Ascaris lumbricoides and cacing tambang 9,67%. This highest infection of STH was found on students of SDN 49/II Senamat, that was Ascaris lumbricoides 32,26% from 62 student.Key words: soil transmitted helminth, student